SPECIFIC FEATURES OF RENDERING EMOTIONALLY CHARGED SYNTACTIC STRUCTURES (International Conference on Economics, Finance, Banking and Management, 2025)
Language is a direct expression of human thought and the inner world. With the help of linguistic means such as sentence structure, word choice, style, tone, a person is able to fully express his opinion, emotion, mood, psychological state. The language allows you to convey the inner experiences of the speaker or writer, his emotional state in a specific style. Especially emotionally charged syntactic structures are widely used in the correct, expressive, and expressive description of various situations in human and social life, as well as individual and collective experiences of individuals. Structures like these come to the surface mainly in the processes of fiction, media, official speech, folk oral creativity and everyday conversation.